2004
DOI: 10.1042/bst0321032
|View full text |Cite
|
Sign up to set email alerts
|

Direct interactions between NMDA and D1 receptors: a tale of tails

Abstract: Considerable evidence has accumulated describing a complex interaction between the dopaminergic and glutamatergic pathways. Efforts to describe the mechanisms underlying this complex interaction have implicated a functional interaction between dopamine and glutamate receptors. Classically, the interaction between D(1) and NMDA (N-methyl-D-aspartate) receptors has been proposed to involve the activation of second-messenger signalling cascades after receptor stimulation. However, in recent years, another paradig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…Previous studies in different cell culture models have focused on the role of NMDA receptor-controlled pathways in the mechanism of Tat neurotoxicity (King et al, 2006;Perez et al, 2001;Wang et al, 1999;Magnuson et al, 1995). There is considerable evidence of functional interactions and cross-talk between NMDA subtype glutamate receptors and dopamine D1-like receptors (Pei et al, 2004;Lee and Liu, 2004;Wirkner et al, 2004). Physical protein-protein interactions also can occur between the NMDA-receptor subunit-1 (NR1) and C-terminal peptides of D1 receptors; suggesting intracellular associations of direct relevance to dopaminergic modulation of NMDA currents (Pei et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in different cell culture models have focused on the role of NMDA receptor-controlled pathways in the mechanism of Tat neurotoxicity (King et al, 2006;Perez et al, 2001;Wang et al, 1999;Magnuson et al, 1995). There is considerable evidence of functional interactions and cross-talk between NMDA subtype glutamate receptors and dopamine D1-like receptors (Pei et al, 2004;Lee and Liu, 2004;Wirkner et al, 2004). Physical protein-protein interactions also can occur between the NMDA-receptor subunit-1 (NR1) and C-terminal peptides of D1 receptors; suggesting intracellular associations of direct relevance to dopaminergic modulation of NMDA currents (Pei et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine-glutamate interactions have been shown in different brain regions. Numerous studies have demonstrated that NMDA receptor function may be regulated by dopamine D1-like receptors, composed of D1 and D5 like receptors (Cepeda and Levine, 1998;Lee and Liu, 2004;Lezcano and Bergson, 2002;Pei et al, 2004;Cepeda and Levine, 2006;Missale et al, 2006). However, it is not known whether D1 dopamine receptors are involved in neurotoxicity of HIV-1 proteins.…”
Section: Introductionmentioning
confidence: 99%
“…DARs can signal through mechanisms independent of the traditional, G protein mediated pathways (Beaulieu et al, 2005;Zou et al, 2005;Lee and Liu, 2004;Pei et al, 2004;Liu et al, 2000;Lefkowitz and Shenoy, 2005). To determine if the DA-induced increase in cAMP is due to Gi/o proteins ( Figure 2) and/or G protein independent cascades, we examined the effect of DA in the presence of PTX, which specifically blocks the activation and dissociation of all members of the Gi/o family, except Gz.…”
Section: The Da-induced Increase In [Camp]i Is Mediated By Gi/o Proteinsmentioning
confidence: 99%
“…Fourth, GPCRs are known to interact directly with target proteins. For example, DARs can physically interact with, and activate ionotropic glutamate receptors (Zou et al, 2005;Lee and Liu, 2004;Pei et al, 2004;Liu et al, 2000). Fifth, GPCRs can activate additional cascades, like the mitogen activated protein kinase (MAPK) cascade via crosstalk (Werry et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…De este modo, anormalidades sutiles en el equilibrio GABA/Glutamato que en etapas pre-adolescentes provocaban síntomas cognitivos y emocionales de intensidad leve a moderada, bajo el influjo de los cambios asociados a la adolescencia, particularmente en la actividad dopaminérgica (69) , podrían llevar a la emergencia de estados hiperglutamatérgicos de intensidad aún mayor. En apoyo a esta hipótesis, una creciente literatura neurocientífica básica indica que la señal dopaminérgica ejerce un poderoso efecto potenciador de la neurotransmisión glutamatérgica a diversos niveles (70) . Así, dada la irreversibilidad de los reajustes sinápticos producidos en esta etapa del desarrollo, es esperable que, de no actuar a tiempo, la pérdida de conectividad producida por esta hiperactividad glutamatérgica alcance un nivel crítico que conduzca a estados de deterioro cognitivo y emocional sobre los cuales sea difícil intervenir una vez superado este período crítico.…”
Section: Retracción Dendrítica Inducida Por Hiperactividad Glutamatérunclassified